مفهوم األمة عند العلواني: رؤية عقدية ومعرفية تجديدية = The concept of Ummah according to Al-Alwani: a renewed epistemic and theological perspective - Al-Sayed Issa, Fida Ad-Din; Abdelaziz, Berghout (IIUM, 2025)
The research examines Dr. Taha Jaber Al-Alwani's significant contributions to modern Islamic thought, focusing on his innovative perspective on the concept of the "Ummah" (community) and its connection to rebuilding. The study explores his cognitive background, ideological foundations, and reviews of key debates in Islamic and Arab thinking, such as self-other dynamics, pluralism, peaceful coexistence, citizenship, and globalism. Dr. Al-Alwani provides a methodological approach from a jurisprudential and purposive perspective. The research concludes by synthesizing key ideas, aiming to interpret the Ummah concept from Dr. Al-Alwani's innovative viewpoint, relying on an inductive and analytical approach based on his publications.